THE GOOD FAITH PRINCIPLE IN TRUST AND CONFIDENTIALITY ON THE ARBITRATION PROCESS - Anangga W. Roosdiono; Maria Jasmine Putri Subiyanto; Muhamad Dzadit Taqwa (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2022)
This article is to demonstrate that the principle of good faith (iktikad baik) manifests in the principles of trust and confidentiality. Not only is good faith one of the key causes of the emergence of a dispute, it also indeed has a great influence on the success of resolving that dispute. Despite its importance, we have found that many disputing parties do not apply this principle to resolve their disputes. Even though, this principle plays a huge part on maintaining trust and confidentiality at the same time. The purpose of this paper is to increase awareness on the application of the good faith principle, noting that there are still realities where this principle is not applied. In this paper, we first elaborate on the descriptive comprehension of all these three principles. Afterwards, we observe how good faith connects with the other two principles. Through the manifestations of good faith, we have concluded that the a quo principle acts as a key basis for the application of the other two principles. In trust, applying good faith means making the arbitration trustworthy, whereas in confidentiality, maintaining good faith keeps the information confidential to irrelevant parties. In the conclusion, we have pointed a few concrete resolutions on maintaining the principle of good faith, trust, and confidentiality. This is found by observing the two factors that cause the realities when the principle of good faith is not applied, which consists of the normative and human factor.